PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN BACK OFFICE DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. BANK TABUNGAN NEGARA (PERSERO), TBK KANTOR CABANG SURABAYA - ARIFAH MAULIDYAH, INDI (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this study is to analyze the effect of job stress on the performance of back office employees with motivation as intervening variable at PT. Bank Tabungan Negara (Persero), Tbk Surabaya Branch Office. Population of this research is permanent employee of back office which amount 50 people, and sample used is saturated sample. In this study using Least Square partial analysis using SmartPLS 3.0 software The result of the study showed that job stress had a significant positive effect on employee performance, job stress had a significant positive effect on motivation, motivation had positive significant effect on employee performance, and job stress had a significant positive effect on employee performance through motivation Keywords: Job Stress, Employee Performance, Motivation